Education and Assistance for Strengthening Micro Business Institution at GKI EMAUS Surabaya (Universitas Negeri Semarang, 2022)
The community service is carried out to increase the knowledge of small business owners related to entrepreneurship. The form of community service implementation has carried out education and assistance to achieve all aspects of business, significantly increasing business profits. The community service partner is a member of the GKI EMAUS church who has a small business in Surabaya. They sell their products in food and beverages with most church members. This series of activities consisted of preparation and implementation until the evaluation phase, which took three months from November 2021 to January 2022. The community activities also involved the students using the service-learning method. The lecturer teams provide the material as the implementation of the course. Furthermore, together with the lecturers, the students did the community service in education and business strengthening for three months. MSME partners from GKI EMAUS feel many benefits, such as recording financial transactions, improving the formation of the right product price, and documenting the products. The results of community service are felt to have a high impact on partners because there have been improvements in small business management and sales.